Centrifugal casting – perspective technology of production of details for agricultural machines - A. A. Andrushevich; A. D. Oсhotsky; M. A. Sadokha (Литьë и металлургия, 2019)
The basic requirements for cast blanks and details of agricultural machinery are considered. The prospects of using the method of centrifugal casting in the production of workpieces for the repair and maintenance of agricultural machinery in Belarus are shown. On the basis of the analysis of a number of details of the agricultural machines having the sufficient program of production the choice of the equipment for centrifugal casting of JSC BELNIILIT’s design was selected.